Mental Accounting and MSME Sustainability: The Mediating Role of Financial Performance toward SDG 8 - Sri Mulyani; Rahmawati Rahmawati; Djuminah Djuminah; Evi Gantyowati; Endang Dwi Amperawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: Examining the effect of mental accounting on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) and investigates the mediating role of financial performance. Given the significant contribution of MSMEs to economic growth and employment, understanding factors that support their long-term sustainability is essential for achieving Sustainable Development Goal (SDG) 8 on sustainable economic growth and productive employment. Method: Employing a quantitative research design using survey data collected from 226 MSME owners in Kudus Regency, Central Java, Indonesia. Respondents were selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Results: The findings reveal that mental accounting has a significant positive effect on both financial performance and MSME sustainability. Financial performance also significantly influences business sustainability and serves as a mediating variable in the relationship between mental accounting and MSME sustainability. These results indicate that MSME owners who effectively plan, manage, and evaluate their financial resources are more likely to achieve stronger financial performance and long-term business sustainability. Novelty: Studying extends the behavioral accounting literature by examining financial performance as a mediating mechanism linking mental accounting and MSME sustainability. The findings provide practical insights for MSME stakeholders and policymakers regarding the importance of financial decision-making behavior in strengthening business resilience and supporting SDG 8.